ISLAMIC HOME FINANCING IN MALAYSIA: AN OVERVIEW OF ISLAMIC FINANCE CONCEPTS APPLIED - Nurjannah Hasmad; Abdulrahman Alosman (al-Afkar, Journal For Islamic Studies, 2022)
Owning a house is an essential decision in one’s life. With various house financing products offered by financial institutions, products that adhere to the Shariah principles or Shariah-compliant became an alternative for Muslim consumers to avoid being involved in transactions related to usury (riba). This paper aims to provide an overview of the Islamic concepts applied in Islamic home financing products in Malaysia namely Ba’I Bithaman Ajil, Musharakah Mutanaqisah and Tawarruq. This study employs the library research method by examining journal articles, books, resolutions, guidelines and policy documents relating to the matter. This study found out that each concept is truly rooted in the Shariah principles despite some issues regarding Shariah compliance rising around it that differ in degrees from each other. It is also found out that even when applying the Shariah concept in the operation of these concepts, banks cannot yet escape from using interest-based benchmarks in calculating their profit. It is concluded that Islamic banks are exerting a commendable effort in providing Shariah alternatives for home financing, however, this effort needs to be continued to provide a Shariah-compliant home financing that at the same time more affordable to consumers than conventional loans.